3D printing of functional nerve guide conduits. Issue 1 (7th May 2021) - Huang, Yulan; Wu, Wenbi; Liu, Haofan; Chen, Yuwen; Li, Bo; Gou, Zhiyuan; Li, Xun; Gou, Maling
Abstract: Nerve guide conduits (NGCs), as alternatives to nerve autografts and allografts, have been widely explored as an advanced tool for the treatment of peripheral nerve injury. However, the repairing efficiency of NGCs still needs significant improvements. Functional NGCs that provide a more favorable microenvironment for promoting axonal elongation and myelination are of great importance. In recent years, 3D printing technologies have been widely applied in the fabrication of customized and complex constructs, exhibiting great potential for tissue engineering applications, especially for the construction of functional NGCs. In this review, we introduce the 3D printing technologies for manufacturing functional NGCs, including inkjet printing, extrusion printing, stereolithography-based printing and indirect printing. Further, we summarize the current methods and strategies for constructing functional NGCs, such as designing special conduit architectures, using appropriate materials and co-printing with different biological cues. Finally, the challenges and prospects for construction of functional NGCs are also presented.